Design Overview Of User Interface Design For Medical Record Filling System At Dharma Yadnya General Hospital - Made Wahyu Aditya (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2025)
The manual recording of borrowing and returning medical record documents using expedition books leads to several challenges, such as incomplete data on borrowing and returning medical record documents beyond 24 hours, as well as delays in returning medical record documents. Additionally, manual expedition book usage is less effective and efficient. The purpose of this research is to understand the overview of designing the user interface for filling system medical record documents. The research method used is descriptive qualitative with the waterfall design method.. The research results indicate that the user acceptance level of the user interface design falls within the acceptable category. This indicates that the user interface design for the electronic expedition system of inpatient medical records has a good level of usability. With an average score of 90, there is no need for further improvements in the user interface design, which can be considered as a recommendation to Dharma Yadnya General Hospital.